2017
DOI: 10.1590/1982-0216201719510817
|View full text |Cite
|
Sign up to set email alerts
|

The opinion of parents and teachers of students with learning disorders regarding executive function skills

Abstract: Purpose: to compare the opinion of parents and teachers of students with learning disorders, regarding executive function skills.Methods: a cross-sectional cohort study, involving 39 students, boys and girls, with a multi-disciplinary diagnosis of learning disorders. Participants in the age range 8 to 11 years and 11 months were enrolled in Grades 3 to 5 of Primary Education I. The Behavior Rating Inventory of Executive Function (BRIEF) questionnaire, comprising one questionnaire for the parents and another fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…The different perceptions about EF between parents and teachers in functional instruments are reported in the literature, such as different kinds of demand and time. In addition, teachers spend less time with the child when compared to parents, and therefore it is expected they will have less knowledge about their behavior, abilities and difficulties (Germano, Brito, & Capellini, 2017;Jarratt et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The different perceptions about EF between parents and teachers in functional instruments are reported in the literature, such as different kinds of demand and time. In addition, teachers spend less time with the child when compared to parents, and therefore it is expected they will have less knowledge about their behavior, abilities and difficulties (Germano, Brito, & Capellini, 2017;Jarratt et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that mainstreaming education could not be realized as desired due to reasons such as the physical structure of the school and the unsuitable class size, the unequal distribution of inclusion students to the classes, the demands of the classroom teachers not being met, insufficient material support, and insufficient inservice trainings despite the fact that the teachers received assistance from the training support teachers (Sarac and Colak 2012;Guzel 2014;Yaman 2017). When the studies were examined in general, it was found that classroom teachers emphasized that they did not find themselves sufficient about inclusion education, that support education services and material support were not provided, and that they wanted to improve themselves in relation to the education of students with special needs but they did not receive education support in this sense (Dagli and Oznacar, 2015;Germano, Brito and Capellini, 2017;Sardohan and Akcamete, 2018;Bayrakli and Sucuoglu, 2018). In order to be effective in mainstreaming education, it is of great importance to determine the actions of classroom teachers regarding instructional practice and evaluation, and to take necessary precautions and to provide the necessary support in this area.…”
Section: Determining Practices Of Classroom Teachers Who Have Mainstreaming and Special Needs Students In Their Classesmentioning
confidence: 99%
“…A large body of studies reveals that, regardless of context, education is only successful if it involves all relevant stakeholders, including parents, teachers, primary caregivers and the students themselves (Hussein et al, 2015). Parent satisfaction is an important factor in evaluating special education services (Samiti et al, 2011; Germano et al, 2017). Thus, the primary goal of this study is to investigate the level of satisfaction of parents of children with LD with the effectiveness of the programme in which their children are enrolled.…”
Section: Introductionmentioning
confidence: 99%